COMPARING THE EFFICACY OF 35% TRICHLOROACETIC ACID (TCA) PEEL WITH TOPICAL 0.1% ADAPALENE GEL IN THE TREATMENT OF COMEDONAL ACNE - RANI , N; HASSAN , T; SHAHZAD , MK; HANIF , N; ULLAH , M; HUMERA , F (Biological and Clinical Sciences Research Journal, 2024)
Comedonal acne is a common dermatological condition characterized by open and closed comedones. Treatment modalities, including chemical peels and topical retinoids, have managed comedonal acne. Aim and Objective: This study aimed to compare the efficacy of 35% trichloroacetic acid (TCA) peel with topical 0.1% adapalene gel in treating comedonal acne. Methodology: A randomized controlled trial (RCT) was conducted at the Sheikh Zayed Hospital, Rahim Yar Khan. A total of 80 patients with comedonal acne were recruited and randomly assigned to two treatment groups: Group A received 35% TCA peel, while Group B received topical 0.1% adapalene gel. The primary outcome measures included changes in comedonal lesion count and severity, assessed using standardized clinical photographs and dermatological examinations. Secondary outcomes comprised patient-reported improvement, adverse events, and treatment tolerability. Results: The mean age of participants was 25.4 ± 4.6 years, with a female predominance (65%). At baseline, both groups exhibited similar comedonal lesion counts and severity scores. Following treatment, a significant reduction in comedonal lesions was observed in both groups (p < 0.001). However, the reduction in comedonal lesion count was more significant in the 35% TCA peel group than the adapalene gel group (mean decrease of 80% vs. 60%, respectively). Additionally, patients in the TCA peel group reported higher satisfaction rates and fewer adverse events than the adapalene gel group. Conclusion: Our study suggests that 35% TCA peel is more effective than topical 0.1% adapalene gel in reducing comedonal acne lesions and improving patient satisfaction. TCA peel may represent a promising treatment option for patients with comedonal acne, offering superior efficacy and tolerability compared to topical retinoids.